Retraction Note: Preservation of dendritic spine morphology and postsynaptic signaling markers after treatment with solid lipid curcumin particles in the 5xFAD mouse model of Alzheimer’s amyloidosis - Panchanan Maiti; Zackary Bowers; Ali Bourcier-Schultz; Jarod Morse; Gary L. Dunbar (Alzheimer’s Research & Therapy, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13195-021-00769-9.